ISSUES CONCERNING TRIPOLYE METALLURGY AND THE VIRGIN COPPER OF VOLHYNIA - Klochko, Viktor I.; Manichev, Vyacheslav I.; Kvasnitsa, Viktor N.; Kozak, Sergey A.; Demchenko, Larisa V.; Sokhatskiy, Mikhail P. (Uniwersytet im. Adama Mickiewicza (Poznań). Instytut Prahistorii, Uniwersytet im. Adama Mickiewicza (Poznań). Instytut Wschodni, 2000)
The ‘western borderland’ of the Tripolye culture, appearing in the title of this volume of the ‘Baltic-Pontic Studies’, refers to the cyrcle of neighbouring cultural systems of the Upper Tisza and Vistula drainages. As neighbours of the Tripolye culture such groups are discussed as Lengyel-Polg´ar, Funnel Beaker and, albeit to a much narrower extent, the Globular Amphora (cf. B-PS vol. 8) and the Corded Ware cultures. The papers discuss the reception of ‘western’ traditions by Tripolye communities as well as the ‘western borderland’ mentioned in the title. Defined in this way, these questions have been only cursorily treated in the literature. The consequences of accumulated omissions in the study of the cultural surroundings of ‘Tripolye’ have been felt by us when we worked on this issue. Thus, we submit a greatly limited work as far as its subject matter is concerned hoping that it will open a sequence of necessary studies. Such studies should, in the first place, focus on the co-ordination of the ‘languages’ of taxonomy and then they should investigate different aspects of the mechanisms of the outlined processes of the ‘cultural contact’.